Economic Fables - Moran, Shane (Kronos: Southern African Histories, 2017)
When the aura of primitive communities involves closeness to nature and egalitarianism it is time to reflect upon the source of this interpretation. What story is being told, and what socio-political moral is being drawn from the image of the IXam garnered from the Bleek and Lloyd archive? What values are being naturalised in an interpretation that foregrounds sympathy as integral to the process of interpretation? What kind of community are author, reader and subject founding?